Bank Forward Lending in Alternative Funding Environments - DESHMUKH, SUDHAKAR D.; GREENBAUM, STUART I.; KANATAS, GEORGE (Journal of Finance, 1982)
ABSTRACT This paper examines the effects of loan commitments on bank lending behavior in both deposit‐funding and liability management environments. Assuming that the bank lends exclusively under commitments and that the number of commitments exercised is uncertain, the bank must choose its supply of commitments. Given this choice, the bank becomes a passive lender to commitment holders. Our focus on forward credit markets sheds new light on the private bankers' assertion that they do not directly determine their level of lending, but merely “accommodate” the credit needs of their customers. Similarly, the central banker's claimed inability to control monetary aggregates in the short‐run becomes understandable in a new context. It is shown that the advent of liability management will reduce the volume of loan commitments and the expected size of the bank and of the banking system. It is also shown that increased uncertainty regarding borrower takedown behavior diminishes the volume of commitments, expected bank and banking system size.